Ukrainian surnames as quasi-genetic markers. The correlation with blood group and Y-chromosome haplogroups - Горпинченко, М. Ю.; Буркова, В. В.; Утєвська, О. М.; Атраментова, Л. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The article substantiates the validity of usage Ukrainian surnames as quasi-genetic markers. The inter-population distances, inbreeding values and ethnic population structure were estimated using the frequency of surnames. The interpopulation distances based on the surnames frequencies correlated positively with the inter-population genetic distances calculated from the allelic frequencies of AB0 and Rh systems (r=0.69; p=0.007), and from the frequencies of Y-chromosome haplogroups (r=0.60; p=0.06). Random inbreeding coefficients obtained from the surnames frequencies, were inversely proportional to population size. The ethnic structure of the most common surnames in Slobozhanschyna, Transcarpathia, Polesie and Zaporozhye reflected objectively the historical and cross-border migrations. In general, Ukrainian surnames provide reliable estimates of a population structure, that confirms the possibility of their use as quasigenetic markers.